Muslim chaplaincy in the UK: the chaplaincy approach as a way to a modern imamate - Hafiz, Asim (Religion, state & society, 2015)
In this article I examine the chaplaincy approach to religious and pastoral leadership in the UK and what the experience may offer to mosque-based imams. I compare the role and tasks of the imam in chaplaincy with the duties of the mosque-based imam. The identity of the Muslim chaplain is made up of various associations' - professional; vocational; religious and communal; educative and reformative - that make him better equipped to offer a contextually relevant imamate, whereas the mosque-based imam has only one association' (the religious and communal) that describes his remit and role, and therefore may not be able to provide a competent imamate which meets the needs of Muslims in the contemporary secular UK.